I27 Participants at the leiden site of the registry study: a demographic approach. (13th September 2016) - Baake, Verena; Hart, Ellen; Bos, Reineke; Roos, Raymund
Abstract : Background: REGISTRY is the largest European observational study of Huntington's disease (HD). The Leiden University Medical Centre (LUMC) in The Netherlands is the largest recruiting site. Objective: The aim of this paper is to give an overview of the baseline characteristics of all Leiden participants from the start of the study in 2005 until the close of REGISTRY at the LUMC in September 2014. Methods: The Leiden cohort is described in two different ways: CAG repeat length and presence of motor signs. Results: Division into groups based on prolonged CAG length revealed that the cohort consists of 4 intermediate – (27–35 CAG), 22 reduced penetrance – (36–39 CAG), 465 full penetrance – (> 39 CAG) and 60 control participants (< 27 CAG). The second way of dividing the participants based on present or absent of motor signs, showed that 170 pre-motormanifest – and 317 motormanifest participants were enrolled. Conclusion: The Leiden REGISTRY cohort at baseline is mainly characterised by full penetrance gene expansion carriers who have been clinically diagnosed with HD but who remain relatively functionally independent. For the majority of these participants, disease onset was based on motor signs followed by psychiatric and cognitive signs.